Modern trends and risks in the development of resource regions of Russia - Irina Ilina; Carol Scott Leonard; Evgenij Pliseckij (European Regional Science Association (ERSA), 2014)
This paper, part of a larger project on governance and growth in Russia. It deals with the problems and priorities of the future development of primary producer regions of Russia. We design a regional strategy for socioeconomic development to 2025-2030. The analysis concerns growth and diversification of the economy of regions, where raw materials are abundant, in order to scale back the exploitation of mineral resources and diversify the economy. Almost all strategies involve a gradual change of the vector in the direction of modernization and diversification of the economy. We emphasize that the important role here is for a new regional policy. The paper examines regional financial resilience in Russia in the period following the global financial crisis. The level of risk is rising, as government emergency finance is withdrawn and regions face rising debt to cover even operational expenses, but "resource" regions seem securely well off, despite having been most affected by the financial crisis. This paper examines one region, Khanty-Mansiysk autonomous okrug (KhMAO), the largest "donor" to the federal budget, against the background of other mineral resource abundant regions. It traces developments since the dramatic budget reforms (late 1990s through 2005), including centralization of revenues and rationalized program expenditure (Alexeev and Weber 2013). It assesses regional budget and debt management in response to pressures from increased federal required expenditures, post-crisis withdrawal of subsidies, and the roll-out of new debt guidelines. It describes and explains KhMAO's stability and relative autonomy in these crisis conditions. The key questions are: Why are these "donor" regions, more affected by the crisis than others, also more resilient? Is Russia's growth core of regions financially stable because of federal intervention? How vulnerable is the resource region to future oil price shocks? Our findings are tenative, since there remain questions about transparency and soft budget constraints (Plekhanov 2006). We show federalism at its most cooperative: among other factors, regional collaborative action fosters flexible budgeting. In the longer run, the resilience of resource regions, such as KhMAO, with their overall steady growth, despite volatility in oil prices, arguably is due geopolitical factors, which attract energy producers and industrial giants other than in the oil sector, and the business environemnt, including steady maintenance of a higher standard of living and skills attracted in new clusters, which are supported by innovation-oriented budgets. The findings here, however, also include, even more fundamentally, an evolvinig cooperative federalist agenda, with groups of regions acting together to secure negotiated decisions on tax allocations and spending requirements. Supportive of the conclusion in Chebankova (2008), the term adaptive federalism applies to finance, and compels a rethinking of the concept of fiscal rigidity as applied to the Russian Federation.
Keywords: R58; R51; H70; 330